Multifunctional Epoxy/Nanocomposites Based on Natural Moroccan Clays with High Antimicrobial Activity: Morphological, Thermal and Mechanical Properties. (22nd November 2019) - Monsif, M.; Zerouale, A.; Kandri, N. Idrissi; Bertani, R.; Bartolozzi, A.; Bresolin, B. M.; Zorzi, F.; Tateo, F.; Zappalorto, M.; Quaresimin, M.; Sgarbossa, P.
Abstract : In this study, a series of new epoxy/clay nanocomposites (ECN) has been prepared and characterized in order to investigate the properties and compare the effect of the unmodified Moroccan clay on the structure and properties of the composite materials. Five natural clays have been used to reinforce the neat epoxy resin with 1% wt and 5% wt achieving the clay dispersion only through strong milling and mechanical stirring without previous organic modifications of the clays. The quality of clay dispersion in the epoxy matrix and the morphology of nanocomposites have been studied by transmission electron microscopy (TEM), environmental scanning electron microscopy (ESEM), and X-ray diffraction (XRD). The mechanical and thermal properties have also been investigated. The antimicrobial activity of the nanocomposites has been tested against E. coli and S. aureus in order to evaluate their applicability as advanced antimicrobial materials. The results showed that the epoxy/crude clay nanocomposites exhibited a high inhibition action attending 99% against both bacteria in the case of the clay labeled A5 .